Agro policy and strategies in Bulgarias cooperative movement - Zaimova, Darina (Economics of Agriculture, 2010)
This paper is firstly aimed to propose a conceptual framework exploring institutional and economic development of cooperative movement in Bulgaria. Secondly it aims to assess the impact of reforms under way in the national economy. The main research questions assign to: Which features of institutional framework hinder or give priority to sustainability of cooperative development? What are responsibilities and interests of public and private sector in shaping the vision of cooperatives? What is the importance of property rights protection to common utilization of agricultural components? The methodology section is based on: a background description of national survey data; an observation of changes in dynamics between formal and informal institutions; in-depth analysis of decision-making process adopted by cooperatives.